2020
DOI: 10.3390/ijms21041216
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Circulating Inflammatory Proteins Following Sport-Related Traumatic Brain Injury

Abstract: Sport-related traumatic brain injury (TBI) elicits a multifaceted inflammatory response leading to brain injury and morbidity. This response could be a predictive tool for the progression of TBI and to stratify the injury of which mild TBI is most prevalent. Therefore, we examined the differential expression of serum inflammatory markers overtime and identified novel markers in repetitively concussed athletes. Neuropsychological assessment by Wechsler Adult Intelligence Scale (WAIS) and Immediate Post Concussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…PEA has been applied to EVs derived from various cell cultures, breast milk, and seminal plasma [ 16 ]. Further, PEA has been used for biomarker discovery related to sports-related brain trauma [ 17 ], chronic mild traumatic brain injury [ 18 ], and Duchenne muscular dystrophy [ 19 ], and could also distinguish patients with Parkinson’s disease from patients with atypical parkinsonisms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEA has been applied to EVs derived from various cell cultures, breast milk, and seminal plasma [ 16 ]. Further, PEA has been used for biomarker discovery related to sports-related brain trauma [ 17 ], chronic mild traumatic brain injury [ 18 ], and Duchenne muscular dystrophy [ 19 ], and could also distinguish patients with Parkinson’s disease from patients with atypical parkinsonisms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21) is a growth factor that enhances metabolic activity and promotes cell growth. Begum et al (2020) found that FGF21 was significantly downregulated in repeatedly concussed patients. Along with MCP-1, FGF21 was found to be negatively correlated with symptoms (e.g., higher protein expression of FGF21 was associated with fewer symptoms).…”
Section: Resultsmentioning
confidence: 97%
“…For example, TBI induces cytokine changes, and thus changes in levels of IL-6 (pro-inflammatory) and IL-10 (anti-inflammatory), among others, may be indicative of depressive symptoms and can be useful in depressive symptom research (Bodnar et al, 2018; Sheikh-Wu et al, 2022). Begum et al (2020) measured FGF21 and MCP-1 among concussed athletes and found that increased serum concentrations of FGF21 and MCP-1 correlated greater likelihood for reporting headache and fatigue. Biomarkers can also provide insight into the effects of the injury and subsequent neuroinflammatory response in the development or improvement in functional outcomes in TBI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in serum levels of LIGHT/TNFSF14 by natalizumab treatment in MS patients suggests that LIGHT/TNFSF14 decreases when inflammation is reduced by disease‐modifying treatment. LIGHT/TNFSF14 was found to be significantly reduced in concussed patients when compared with healthy individuals 21 . LIGHT/TNFSF14 engages two cellular signaling receptors, lymphotoxin receptor (LTR) and HVEM, and is inactivated by Decoy receptor‐3 (DcR3) 22 .…”
Section: Discussionmentioning
confidence: 99%